Electrical model of the 90 nm MOSFET - A. M. Borovik; V. T. Khanko; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The technique of extraction and identification of electrical models parameters for nanoscale semiconductor devices based on optimization methods application is developed. The proposed approach efficiency to identification, extraction and optimization of parameters of semiconductor devices electrical models is demonstrated by examples of BSIM4 and HiSIM2 models SPICE parameters extraction for standard design MOS transistors manufactured using the technology providing minimum channel length of 90 nm.